2005
DOI: 10.1167/iovs.04-0932
|View full text |Cite
|
Sign up to set email alerts
|

TNF−857T, a Genetic Risk Marker for Acute Anterior Uveitis

Abstract: A significant difference in the frequency of TNF-857T allele was found in patients with IAU. There was a trend toward the development of inflammation-related complications in HLA-B27(+) patients with IAU who were carriers of TNFRSF1A-201T or TNFRSF1A-1135T alleles. Genetic variations in these proinflammatory mediators and their receptors appear to influence the susceptibility and severity of the inflammatory response within the eyes of patients during the development of IAU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 48 publications
1
23
0
1
Order By: Relevance
“…After 7 days, the six eyes were enucleated, incised at the limbus and fixed for 1 h at 4 1C in 2% paraformaldehyde and 0.2% glutaraldehyde in phosphate-buffered saline (PBS). They were rinsed three times in PBS before being incubated overnight at room temperature with 1 mg ml À1 X-gal (5-bromo-4-chloro-3-indolyl galactopyranoside; SigmaAldrich, Saint-Quentin-Fallavier, France) in PBS containing 5 mM of K 3 Fe(CN) 6 , 5 mM of K 4 Fe(CN) 6 , 2 mM of MgCl 2 and 0.02% NP-40. After washing with PBS, direct imaging from the outside the eyes was carried out using a numerized camera (Coolpix; Nikon, Fnac, Paris, France).…”
Section: Electrotransfer To Rat Ciliary Musclementioning
confidence: 99%
See 1 more Smart Citation
“…After 7 days, the six eyes were enucleated, incised at the limbus and fixed for 1 h at 4 1C in 2% paraformaldehyde and 0.2% glutaraldehyde in phosphate-buffered saline (PBS). They were rinsed three times in PBS before being incubated overnight at room temperature with 1 mg ml À1 X-gal (5-bromo-4-chloro-3-indolyl galactopyranoside; SigmaAldrich, Saint-Quentin-Fallavier, France) in PBS containing 5 mM of K 3 Fe(CN) 6 , 5 mM of K 4 Fe(CN) 6 , 2 mM of MgCl 2 and 0.02% NP-40. After washing with PBS, direct imaging from the outside the eyes was carried out using a numerized camera (Coolpix; Nikon, Fnac, Paris, France).…”
Section: Electrotransfer To Rat Ciliary Musclementioning
confidence: 99%
“…3,4 Furthermore, polymorphisms within the TNF-a promoter region and the TNF-a receptors genes have been associated with a significant increased susceptibility for developing intraocular inflammation in HLA-B27 + patients. 5,6 Based on these initial findings, pilot studies have demonstrated the efficacy of anti-TNFa strategies for the treatment of refractory uveitis using either etanercept (a p75 TNF receptor fusion protein), infliximab (a chimeric immunoglobulin G (IgG) monoclonal antibody (mAb) directed against TNF-a) or adalimumab (a human monoclonal TNF-a antibody). 7,8 In these patients systemic administration of antibodies directed toward TNF-a (infliximab or adalimumab) appeared more beneficial than the administration of the p75 TNF soluble receptor fusion protein (etanercept).…”
Section: Introductionmentioning
confidence: 99%
“…This polymorphism may be linked to an alteration in the binding of a repressor in the promoter region of the TNF gene. 96 Additional analysis of the 874T allele of the IFN-γ gene, which reflects a constitutively higher production of IFN-γ, has shown that it is more prevalent in patients with idiopathic intermediate uveitis as compared to controls. 97 A significant association between IL-10-1082 AA homozygosity and poor visual outcome has also been shown.…”
Section: Cytokines and Chemokines In Patients With Uveitismentioning
confidence: 99%
“…Third, after adjustment for multiple testing, PsA, but not psoriasis vulgaris, is significantly associated with the minor allele of the TNF-857 promoter polymorphism, and this association is independent of the PSORS1 risk factor. The latter finding is of particular interest, since carriage of TNF*-857T has already been associated with other diseases characterized by increased production of TNF␣, such as inflammatory bowel disease (11), acute uveitis (14), and gastric B cell lymphoma (15), indicating the biologic relevance of this polymorphism. For PsA, concurrent findings of association of TNF*-857T have more recently been made in a study of considerably smaller cohorts of probands in Toronto, Ontario, Canada (203 PsA patients and 100 healthy controls) (8).…”
Section: Discussionmentioning
confidence: 99%
“…The most critical issue in this respect is evidence of a rather high long-range linkage disequilibrium (LD) at 6p21, affecting HLA-C as well as the genes TNF and LTA, which encodes lymphotoxin ␣ (previously known as TNFB) (10). Furthermore, circumstantial evidence suggests that TNF polymorphisms other than the most frequently investigated SNPs at positions -238 and -308 might also have an impact on a broad range of inflammatory conditions (11)(12)(13)(14)(15), indicating the requirement for an extended investigation of TNF variants. Moreover, the observation that variants of TNFRSF1B, which encodes TNF receptor superfamily member 1B, might have functional consequences on the levels of the soluble receptor protein in the circulation (16) as well as evidence of an association of the TNFRSF1Bϩ676 polymorphism with rheumatoid arthritis (17) strongly support the inclusion of SNPs of the TNF receptor genes (TNFRSF1A and TNFRSF1B) in a genetic association study.…”
Section: Hla-bmentioning
confidence: 99%